Analysis of the determinants of fertility decline in the Czech Republic - Stephan Klasen; Andrey Launov (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2003)
In this paper we study the decline in total fertility rates in the Czech Republic during the transition process. To identify transition-specific features of this decline we use a multiperiod model of birth process and apply it to the family and fertility survey of 1998. In a standard duration analysis setting the model allows for time-dependence of information sets, on which the decision about the next birth is made. It also enables to estimate probabilities of early exit from childbearing. In this work we find that the negative effect of transition on TFR is mostly translated through a sharply increased negative influence of higher education on fertility, and through the apparent lack of adequate childcare facilities.
urn:nbn:de:bvb:19-epub-1727-3
Keywords: J13; J11; 519; Fruchtbarkeit; Übergangswirtschaft; Schätzung; Tschechische Republik